PENINGKATAN PEMAHAMAN RESENSI MENGGUNAKAN MODEL PEMBELAJARAN COURSE REVIEW HORAY PADA SISWA KELAS XI SMA NEGERI 1 LAWE ALAS TAHUN PEMBELAJARAN 2021/2022 - Nirma Al Adawiyah; James Marudut; Irfan Johari (STKIP USMAN SAFRI KUTACANE, 2022)
Nirma Al Adawiyah, NIM. 17317001030. Improving Reviewer Understanding Using the Course Review Horay Learning Model for Class XI Students at SMA Negeri 1 Lawe Alas, Academic Year 2021/2022 This study aims to determine the improvement of reviewer understanding using the Course Review Horay learning model in class XI students of SMA Negeri 1 Lawe Alas in the 2021/2022 academic year. The number of samples in this study were 28 students, namely class XI IPS 1 . Based on the results of the research and discussion that have been described in the previous chapter, it can be concluded that the Improvement of Reviewer's Understanding Using the Course Review Horay Learning Model for Class XI Students of SMA Negeri 1 Lawe Alas in the 2021/2022 Academic Year. This is evident from the average value of the initial test of Improved Understanding of Student Reviewers is 58.21 with a standard deviation of 7.93 and an increase in the final test result score with an average value of 79.29 with a standard deviation of 5.93. and if it is associated with the Indonesian KKM score for senior high school of 75, the Improvement in Reviewer Understanding for the student's final test is included in good ability. In addition, the observation value > ttable which is 11.14 > 2.05, thus from the results of testing the hypothesis above, it can be concluded that there is an increase in reviewer understanding using the Course Review Horay Learning Model in Class XI students of SMA Negeri 1 Lawe Alas in the 2021/2022 academic year.